Effects of exercise interventions on physical function, cognitive function and quality of life of frail older adults in nursing homes: a systematic review and meta-analysis - Zhu, Yingbo; Zhang, Yu; Li, Xiao; Du, Zhijuan (Frontiers in Psychology, 2025)
ObjectiveOlder adults often face frailty as they age, characterized by a decline in physical and mental health, leading to increased reliance on caregiving services, particularly in nursing homes. Exercise interventions have emerged as an effective means of improving health outcomes, but their efficacy for this population remains unclear. The aim of this study was to investigate the effects of exercise interventions on physical function, cognitive function and quality of life of frail older people in a nursing facility.MethodsData were systematically collected from five major databases and analyzed using RevMan 5.4 and Stata 17.0. Standardized mean differences (SMD) with 95% confidence intervals were calculated to evaluate health outcomes—including physical function, cognitive function, and quality of life—among frail older adults, and heterogeneity was assessed using the I2 statistic.ResultsA total of 16 studies comprising 1,444 participants (mean age ranging from 73.3 ± 6.4 to 87.3 ± 5.3 years) were included in the meta-analysis. The findings consistently demonstrated that exercise interventions produced significant improvements across multiple domains, including physical performance [SMD = 0.54, 95% CI (0.38, 0.70), p < 0.001], mobility [SMD = −2.42, 95% CI (−3.96, −0.87), Z = 3.07, p < 0.05], muscle strength [SMD = 2.00, 95% CI [0.32, 3.68], p < 0.05], quality of life [SMD = 1.94, 95% CI (0.37, 3.51), p < 0.05], and cognitive function [SMD = 0.64, 95% CI (0.13, 1.15), p < 0.05]. Notably, physical activity yielded pronounced benefits in alleviating depression [SMD = −0.78, 95% CI (−1.07, −0.49), p < 0.001] and frailty [SMD = −1.44, 95% CI (−1.74, −1.15), p < 0.001].ConclusionThis study demonstrated that exercise interventions significantly improve physical function, mobility, grip strength, and lower limb strength. The results also showed positive effects on alleviating depressive symptoms and improving frailty status. With effect sizes indicating a substantial impact. Furthermore, subgroup analysis revealed that a regimen of at least three sessions per week, each lasting no less than 40 min, was associated with the most favorable outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024614885, ID: 614537.